If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + 3) + -5(2x + 1) = 27 Reorder the terms: 4(3 + 5x) + -5(2x + 1) = 27 (3 * 4 + 5x * 4) + -5(2x + 1) = 27 (12 + 20x) + -5(2x + 1) = 27 Reorder the terms: 12 + 20x + -5(1 + 2x) = 27 12 + 20x + (1 * -5 + 2x * -5) = 27 12 + 20x + (-5 + -10x) = 27 Reorder the terms: 12 + -5 + 20x + -10x = 27 Combine like terms: 12 + -5 = 7 7 + 20x + -10x = 27 Combine like terms: 20x + -10x = 10x 7 + 10x = 27 Solving 7 + 10x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 10x = 27 + -7 Combine like terms: 7 + -7 = 0 0 + 10x = 27 + -7 10x = 27 + -7 Combine like terms: 27 + -7 = 20 10x = 20 Divide each side by '10'. x = 2 Simplifying x = 2
| 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 | | -7x+2.3=7x-7.9 | | -14-(-3)= | | -28+8x=4-6(2-2x) | | x^2+kx+(k+1)=0 | | 14(12k-12)+14(-10k-11)=42 | | -2.5x+18-1.6x=57 | | 30-4n=-(n-6) | | -2(2t+8)=-28 | | (4x-4)(3x-7)= | | -52=a-11 | | 14+(4p+46)+0= | | 5-(x+3)=6 | | 6[4+7(3-2)]= | | -52=-11 | | 3(-5-12m)-12(2m-1)=-63 | | 101=5y+16 | | (c-25)(c+5)=0 | | 5x+4+3x+8=28 | | 34.6+4h=42.2 | | -104=8a+4(2a+2) |